High-level expression of leghemoglobin in Kluyveromyces marxianus by remodeling the heme metabolism pathway - Tian, Tian; Wu, Xinwei; Wu, Pingping; Lu, Xinyi; Wang, Qi; Lin, Yifan; Liu, Canjie; Zhou, Jungang; Yu, Yao; Lu, Hong (Frontiers in Bioengineering and Biotechnology, 2024)
Soy leghemoglobin, when bound to heme, imparts a meat-like color and flavor and can serve as a substitute for animal-derived proteins. Enhancing cellular heme synthesis improves the recombinant expression of leghemoglobin in yeast. To achieve high-level expression of leghemoglobin A (LBA) in Kluyveromyces marxianus, a food-safe yeast, large-scale heme synthesis modules were transferred into K. marxianus using yeast artificial chromosomes (KmYACs). These modules contained up to 8 native and heterologous genes to promote the supply of heme precursors and downstream synthesis. Next, eight genes inhibiting heme or LBA synthesis were individually or combinatorially deleted, with the lsc1Δssn3Δ mutant yielding the best results.Subsequently, heme synthesis modules were combined with the lsc1Δssn3Δ mutant. In the resulting strains, the module genes were all actively expressed. Among these module genes, heterologous S. cerevisiae genes in the downstream heme synthesis pathway significantly enhanced the expression of their counterparts in K. marxianus, resulting in high heme content and LBA yield. After optimizing the medium recipe by adjusting the concentrations of glucose, glycine, and FeSO4•7H2O, a heme content of 66.32 mg/L and an intracellular LBA titer of 7.27 g/L were achieved in the engineered strain in a 5 L fermentor. This represents the highest intracellular expression of leghemoglobin in microorganisms to date. The leghemoglobin produced by K. marxianus can be utilized as a safe ingredient for plant-based protein products.